Tissue sodium storage: evidence for kidney-like extrarenal countercurrent systems? - Hofmeister, Lucas H.; Perisic, Stojan; Titze, Jens (Pflügers Archiv: European Journal of Physiology, 2015)
Recent evidence from chemical analysis of tissue electrolyte and water composition has shown that body Na(+) content in experimental animals is not constant, does not always readily equilibrate with water, and cannot be exclusively controlled by the renal blood purification process. Instead, large amounts of Na(+) are stored in the skin and in skeletal muscle. Quantitative non-invasive detection of Na(+) reservoirs with sodium magnetic resonance imaging ((23)NaMRI) suggests that this mysterious Na(+) storage is not only an animal research curiosity but also exists in humans. In clinical studies, tissue Na(+) storage is closely associated with essential hypertension. In animal experiments, modulation of reservoir tissue Na(+) content leads to predictable blood pressure changes. The available evidence thus suggests that the patho(?)-physiological process of Na(+) storage might be of relevance for human health and disease.
EVALuna2:3756